2013
DOI: 10.5901/ajis.2013.v2n11p168
|View full text |Cite
|
Sign up to set email alerts
|

Socio - Religious Implications of Child Adoption in Igboland South Eastern Nigeria

Abstract: Child adoption is a challenging social process in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 4 publications
0
10
0
Order By: Relevance
“…This same communal nature underpins many foster parent–child relationships. Each individual belongs to a community of people or family 20 , 33 who have a stake in major life decisions 2 , 24 and reflects in what the Zulu tribe from South Africa refer to as ‘ubuntu’ (I am because you are). The role of family and friends is recognized and far-reaching and reflects in the observation that only a few respondents felt they could not be bothered by the reaction of their family and friends if they were to consider keeping their unintended pregnancies and giving up the child for adoption.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This same communal nature underpins many foster parent–child relationships. Each individual belongs to a community of people or family 20 , 33 who have a stake in major life decisions 2 , 24 and reflects in what the Zulu tribe from South Africa refer to as ‘ubuntu’ (I am because you are). The role of family and friends is recognized and far-reaching and reflects in the observation that only a few respondents felt they could not be bothered by the reaction of their family and friends if they were to consider keeping their unintended pregnancies and giving up the child for adoption.…”
Section: Discussionmentioning
confidence: 99%
“…9 In spite of the fact that the major religious groupings in the world generally accept child adoption in doctrine, 18,19 many studies, including those among West African women, on how adoption could be used to resolve infertility (not for resolving unintended pregnancy crises) showed low acceptance for child adoption. 8,14,16,[20][21][22][23][24] In contrast, a Ghanaian study reported that interest was shown for adopting children from an urban orphanage but one of the main difficulties encountered was unavailability of children meeting the preferences of adopters. 15 Literature search did not reveal any African study on the acceptability of keeping an unintended pregnancy, giving birth and putting the child up for adoption as an unintended pregnancy management option.…”
Section: Resolving Unintended Pregnancy Crisis: Is Adoption a Viable mentioning
confidence: 99%
“…The Christian religion discourages discrimination against an adopted child. Therefore, it is expected that an adopted child should enjoy the same rights and privileges as the biological child in the family setting 21 . Alternatively, Christianity encourages trusting and waiting on God for a child.…”
Section: Peculiarities and Challenges Of Child Adoption In Nigeriamentioning
confidence: 99%
“…As such, various reproduction options have been debated and discussed in the literature. Over the years, adoption has been one of the most popular routes taken by couples in Nigeria struggling with bearing children 6 , however, as practices such as surrogacy become more globally popular, it is crucial to examine popular perceptions about the process and how it fits into the socio-cultural framing of reproduction in Nigeria. Notwithstanding the popularity of adoption, it is a very challenging and complex process to embrace in Nigeria as a result of various stigma and stereotypes 7 .…”
Section: Introductionmentioning
confidence: 99%